2015
DOI: 10.1001/jamaoto.2015.1670
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Predictors of Sensorineural Hearing Loss in Children With Congenital Diaphragmatic Hernia

Abstract: IMPORTANCE Although congenital diaphragmatic hernia (CDH) may be associated with sensorineural hearing loss (SNHL), to our knowledge, no studies have yet identified the pattern of this hearing loss or definitive independent risk factors that may place this population at higher risk. OBJECTIVE To characterize the type and degree or SNHL in CDH survivors and better characterize perinatal risk factors. DESIGN, SETTING, AND PARTICIPANTSThis was a retrospective cohort study of CDH survivors who had a pure-tone audi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
0
14
1
Order By: Relevance
“…Hearing impairment in these babies could be due to fetal hypoxia caused by these comorbid conditions which can lead to damage to cochlear cells and neuronal pathways. 16,20,21 In our study, 15.78% (n = 6) of hearing impaired babies were having meningitis / culture positive sepsis. ALHarbi M et al, KY Chan et al and Meyer A et al concluded that bacterial meningitis is significant factor associated with failed ABR in new born screening, probably due to vasculitis of inner ear or adhesions comprising eighth nerve.…”
Section: Discussionmentioning
confidence: 51%
“…Hearing impairment in these babies could be due to fetal hypoxia caused by these comorbid conditions which can lead to damage to cochlear cells and neuronal pathways. 16,20,21 In our study, 15.78% (n = 6) of hearing impaired babies were having meningitis / culture positive sepsis. ALHarbi M et al, KY Chan et al and Meyer A et al concluded that bacterial meningitis is significant factor associated with failed ABR in new born screening, probably due to vasculitis of inner ear or adhesions comprising eighth nerve.…”
Section: Discussionmentioning
confidence: 51%
“…One of the patients with DS was noted to have Sensorineural hearing loss (SNHL) at birth. Though SNHL has a known association with CDH and is often diagnosed in the toddler years 7 , audiograms are not routinely performed at our institution Survival rates among CDH patients vary widely from institution to institution, but 80% is the most often quoted number for patients who are cared for at a tertiary referral center 8 , which is consistent with our overall survival rate of 83.3%, which is most likely slightly higher than the world average as most of our patients are late presenters. The clear majority of the literature comes from institutions with access to Extra Corporal Membrane Oxygenation (ECMO), which is not available in our setting.…”
Section: Discussionmentioning
confidence: 99%
“…73 Although earlier studies tend to present a higher prevalence of SNHL, Amoils and coworkers report a prevalence of SNHL over 50% in 2015. 74 Controversies exist on the impact of the diagnosis of CDH on the risk of SNHL development. In a study on 111 ECMO graduates, Fligor and coworkers reported a 26% overall prevalence of SNHL in neonates with severe respiratory distress and described CDH as an independent risk factor.…”
Section: Literature Review Pulmonary Function a Literature Overview mentioning
confidence: 99%
“…Most studies with data from neonatal hearing screening, report normal findings. 73,74,[77][78][79][80][81] Therefore, the extreme variability in length of follow-up in available reports, precludes firm conclusions on the actual prevalence.…”
Section: Literature Review Pulmonary Function a Literature Overview mentioning
confidence: 99%
See 1 more Smart Citation